Axitinib plus pembrolizumab in patients with advanced renal-cell carcinoma: Long-term efficacy and safety from a phase Ib trial. (March 2021) - Atkins, Michael B.; Plimack, Elizabeth R.; Puzanov, Igor; Fishman, Mayer N.; McDermott, David F.; Cho, Daniel C.; Vaishampayan, Ulka; George, Saby; Tarazi, Jamal C.; Duggan, William; Perini, Rodolfo; Thakur, Mahgull; et al.
Abstract: Background: Axitinib plus pembrolizumab showed superior overall survival (OS), progression-free survival (PFS) and objective response rate (ORR) versus sunitinib in a randomised phase III trial in patients with advanced renal-cell carcinoma (RCC). We report long-term efficacy and safety of the axitinib/pembrolizumab from the phase I trial (NCT02133742), after 46–55 months from study initiation (data cut-off date, 23rd July 2019). Methods: Fifty-two treatment-naïve patients with advanced RCC were treated with oral axitinib 5 mg twice daily and intravenous pembrolizumab 2 mg/kg every 3 weeks. PFS, duration of response (DoR) and OS were summarised using the Kaplan–Meier method. Results: At a median follow-up of 42.7 months (95% confidence interval [CI]: 41.1–44.1), median OS was not reached; 38 (73.1%) patients were alive. The probability of being alive at 4 years was 66.8% (95% CI: 49.1–79.5). Median PFS in the overall population was 23.5 months (95% CI: 15.4–30.4). ORR was 73.1%; five patients had complete response. Median DoR was 22.1 months (95% CI: 15.1–34.5). Grade III/IV adverse events (AEs) were reported in 38 (73.1%) patients and 20 (38.5%) discontinued treatment because of AEs: 17 (32.7%) discontinued axitinib, 13 (25.0%) discontinued pembrolizumab, and 10 (19.2%) discontinued both drugs. Common AEs included diarrhoea (84.6%), fatigue (80.8%), hypertension (53.8%), cough (48.1%) and dysphonia (48.1%). There were no new AE terms reported and no treatment-related deaths. Conclusions: In patients with advanced RCC with 4 years of follow-up, combination axitinib/pembrolizumab continued to demonstrate clinical benefit, with no new safety signals. Highlights: Axitinib plus pembrolizumab combination therapy provided long-term clinical benefit. Most patients remained alive after approximately 4 years of follow-up. Most patients achieved objective response and responses were durable. There were no new adverse events and no treatment-related deaths.